Research on VoNR solution application - Bei LI; Guanghai LIU; Tian XIAO; Yuhua HU; Hangbo ZHENG; Chen CHENG; Yifan WU; Xiuzhen HUANG (Dianxin kexue)
In the 5G era, in order to improve user perception, shorten call setup delay, and enhance the clarity of real-time voice communication, 3GPP standard introduces the VoNR solution.VoNR is to allow voice, video and data services to be carried on the 5G network, let users experience the high-definition and high-quality audio and video call services, and enjoy 5G high-speed data Internet services while calls.The VoNR technical characteristics and the VoNR solution implementation effect were deeply analyzed.The current challenges faced by the VoNR solution were presented, which provided technical reference for the subsequent nationwide implementation of VoNR.